The economics of CO2 emissions trading for aviation - Peter Morrell (Organisation for Economic Co-operation and Development (OECD), Joint Transport Research Centre (JTRC), 2009)
There has been a growing interest in the environmental impact of aviation, both in terms of noise and aircraft engine emissions. Discussions have included both mitigation measures and methods of internalisation of these environmental costs also described as the principle of polluter pays. This paper focuses on CO2 emissions from aircraft engines, which have both local and climate change implications, and where the emphasis of most recent discussions has centred. These have taken place at an international, regional and local level.
Keywords: 330